1993
DOI: 10.1017/s0252921100029341
|View full text |Cite
|
Sign up to set email alerts
|

Observations of X-Ray Jets Using Yohkoh Soft X-Ray Telescope

Abstract: Time series of SXT (Soft X-ray Telescope) images have revealed many jet-like features in the solar corona. Typical size of the “jet” is 5 × 103 – 4 × 105 km, the typical projected velocity is 30 – 300 km/s, and the kinetic energy estimated to be 1025 – 1028 erg. Many of the jets are associated with flare-like bright points or sub-flares. Three typical examples are discussed, including an X-ray jet identified with an Hα surge. It is suggested that magnetic reconnection is one of the possible mechanisms to produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
116
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(120 citation statements)
references
References 4 publications
4
116
0
Order By: Relevance
“…In the X-ray range, Yohkoh/SXT frequently observed small-scale SXR ejecta, including erupting loops, blobs that were interpreted as plasmoids (with typical speeds of ≈ 500 km s -1 ; see e.g., Shibata et al, 1995;Ohyama and Shibata, 1998), and jets (e.g., Shibata et al, 1992;Alexander and Fletcher, 1999). There has been evidence for the generation of metric type II bursts by these rapidly expanding loops, plasmoids, and jets (Gopalswamy et al, 1997;Klein et al, 1999;Gopalswamy et al, 2001b;Klassen et al, 2003).…”
Section: Small-scale Ejectamentioning
confidence: 99%
“…In the X-ray range, Yohkoh/SXT frequently observed small-scale SXR ejecta, including erupting loops, blobs that were interpreted as plasmoids (with typical speeds of ≈ 500 km s -1 ; see e.g., Shibata et al, 1995;Ohyama and Shibata, 1998), and jets (e.g., Shibata et al, 1992;Alexander and Fletcher, 1999). There has been evidence for the generation of metric type II bursts by these rapidly expanding loops, plasmoids, and jets (Gopalswamy et al, 1997;Klein et al, 1999;Gopalswamy et al, 2001b;Klassen et al, 2003).…”
Section: Small-scale Ejectamentioning
confidence: 99%
“…In particular, we now know that the term "quiet Sun" is not really adequate to describe the coronal field even outside of ARs, since numerous dynamic phenomena on small scales are known to occur there (Schadee et al 1983;Parker 1988;Shibata et al 1992). Chesny et al (2013) found the first evidence for sigmoidal (i.e., S shaped) loops in the QS using SDO/AIA data.…”
Section: Small-scale Dynamicsmentioning
confidence: 99%
“…Moreover, the influence of the individual jets was discernible as fine structures in the solar wind flow at a distance of one AU. Later, X-ray jets were observed by Shibata et al (1992Shibata et al ( , 1994, although not necessarily in quiet-Sun regions. Yokoyama and Shibata (1995) carried out 2D resistive MHD simulations including a simplified convection zone, photosphere, chromosphere and corona.…”
Section: Jetsmentioning
confidence: 99%
“…This has been proposed as the process that heats both the non-flare [e.g., Parker, 1972Parker, , 1979Parker, , 1983Sturrock and Uchida, 1981;van Ballegooijen, 1986;Antiochos, 1990] and flare corona [e.g., Sweet, 1958;Parker, 1963;Petschek, 1964;Carmichael, 1964;Sturrock, 1966] Second, reconnection can produce strong mass motions, the so-called reconnection jets. These have been proposed [Karpen, Antiochos, and DeVore, 1995, 1998] as the explanation for a large variety of transient dynamic phenomena ranging from spicules [e.g., Blake and Sturrock, 1985] to explosive events [Dere et al, 1991] to large surges and sprays [e.g., Rust, 1968;Herant et al, 1991;Schmeider et al, 1994;Yokohama and Shibata, 1996] and X-ray jets [Shibata et al, 1992]. Third, reconnection can lead to the acceleration of non-thermal particles.…”
Section: Introductionmentioning
confidence: 99%